Protection against Anthrax by Needle-Free Mucosal Immunization with Human Anthrax Vaccine - Zeng, Mingtao (2007)
Human vaccination with BioThrax™ requires six injections followed by annual boosters. This makes it difficult for the compliance of the immunization program and underscores the need for development of a new and optimized vaccination protocol. Current research aims to demonstrate the proof of concept to develop a needle free mucosal immunization protocol using a murine anthrax model. A/J mice were immunized with BioThrax™ via an intranasal route. Sera, saliva, vaginal, and nasal washes were evaluated for protective antigen (PA) specific antibody responses by ELISA. Antigen-specific, antibody-secreting lymphocytes were measured by ELISPOT. Sera neutralization antibody titers were determined by in vitro anthrax lethal toxin (Letx) neutralization assay. Immunized animals were challenged by a lethal dose of Bacillus anthracis Sterne spores to determine the efficacy of the vaccination. Nasal mucosal immunization with BioThrax™ elicited robust serum and mucosal antibody responses against PA. The antigen specific antibodies neutralized anthrax Letx, as demonstrated by in vitro neutralization assays. Two doses of intranasal BioThrax™ were sufficient to completely protect A/J mice against challenge with 100×LD ( 50 )Bacillus anthracis Sterne spores. The data suggests that intranasal administration may be an effective immunization modality for an improved immunization program against anthrax.